(untitled) (The Pretoria Student Law Review, 2021)
Is the sale of immovable property, voetstoots, the law of legend? To answer this question properly, let us refer to the definition of a voetstoots clause and then assess how the Consumer Protection Act (herein after referred to as the CPA) applies to the voetstoots clause in a modern-day business transaction regarding immovable property. A voetstoots clause is a clause which is inserted into the contract of sale during the sale of immovable property. It provides that the property in question is sold, ‘as it stands and with all faults’. This means that property, in most cases a house, is sold as it is, completely disregarding any defects the house may have. Defects can be anything from a faulty geyser to decommissioned plug points in one’s new living room. Such a sale of property will not, however, be accepted without scrutiny due to the consumer-friendly legislation enacted under the Constitution, namely the CPA. For easy reference, an example of a voetstoots clause will be included: ‘The property is sold voetstoots in the condition in which it stands and the seller gives no warranty with regard thereto, whether express or implied.’ The question that needs to be asked: ‘Can a voetstoots clause still be valid under the CPA?’ The answer is: Yes, unless you are a developer, investor or speculator.